ISOLATION, IDENTIFICATION AND SENSITIVITY TEST OF BACTERIA FROM DIARRHEA CASES IN DOG AT THE VETERINARY CLINIC, FACULTY OF VETERINARY MEDICINE, GADJAH MADA UNIVERSITY - Yuriadi Yuriadi; Ida Tjahajati (Jurnal Sain Veteriner, 1999)
A study was conducted to find out bacteria which probably play an important role in causing diarrhea in dog at the veterinary clinic Gadjah Mada University. Sample were collected from diarrhea cases of dog, during the periode of September to December 1997, by rectal swabbing. Samples were then sent to the laboratory for bacterial isolation and identification.The result indicated that E. coli was found from 50% of the sample, Streptococcus sp 41.9%, Staphylococcus sp 33.3% of sample, Enterobacter sp 16.7%, Bacillus sp 8.3%.Some of E. coli isolates were pathogenic to mice. The pathogenic E. coli were resistant to penicillin, ampicillin, streptomycin, erythromycin, doxycycline, besides sensitive to neomycin, gentamycin, kanamycin, polymyxin B, chloram-phenicol and sulfisoksale.